Historical Foundations of the Person-Oriented Approach - Subhonova Anora Akmal qizi (Zien Journals, 2023)
The article discusses the historical foundations of the person-oriented approach and the works of scholars who contributed to its development. Basically, the role and importance of the person-oriented approach in the works of our great ancestors, foreign and national scientists has been highlighted.
Keywords: Person-oriented approach; freedom of teaching; humanist; philosophy